Bison Reintroduction to Mixed-Grass Prairie Is Associated With Increases in Bird Diversity and Cervid Occupancy in Riparian Areas - Boyce, Andy J.; Shamon, Hila; McShea, William J. (Frontiers in Ecology and Evolution, 2022)
Rewilding seeks to support and conserve biodiversity through the restoration of natural processes; these goals are often attained through the reintroduction of wildlife. In grassland ecosystems, grazing by large herbivores is a highly influential process that affects biodiversity by modifying the vegetative environment through selective consumption. Here, we test whether rewilding efforts (reintroduction of bison) are associated with increased bird diversity and cervid occupancy in networks of riparian habitat within a temperate grassland ecosystem, mixed-grass prairie in northcentral Montana, USA. We used a long time-series of remote sensing imagery to examine changes in riparian vegetation structure in stream networks within bison and cattle pastures. We then assessed how vegetation structure influenced diversity of bird communities and detection rates of mammals in these same riparian networks. We found that percent cover of woody vegetation, and native grasses and forbs increased more rapidly over time in bison pastures, and that these changes in vegetation structure were associated with increased bird diversity and cervid occupancy. In conclusion, bison reintroduction appears to function as a passive riparian restoration strategy with positive diversity outcomes for birds and mammals.